2013
DOI: 10.1155/2013/908610
|View full text |Cite
|
Sign up to set email alerts
|

In-Patient Treatment of Fibromyalgia: A Controlled Nonrandomized Comparison of Conventional Medicine versus Integrative Medicine including Fasting Therapy

Abstract: Fibromyalgia poses a challenge for therapy. Recent guidelines suggest that fibromyalgia should be treated within a multidisciplinary therapy approach. No data are available that evaluated multimodal treatment strategies of Integrative Medicine (IM). We conducted a controlled, nonrandomized pilot study that compared two inpatient treatment strategies, an IM approach that included fasting therapy and a conventional rheumatology (CM) approach. IM used fasting cure and Mind-Body-Medicine as specific methods. Of 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 29 publications
0
41
0
1
Order By: Relevance
“…After the removal of duplicates, a total of 7080 studies was identified in the search. Following full‐text screening, 71 studies were identified for inclusion, with 23 eligible for meta‐analysis. The abstracts for the majority of the papers were not sufficiently detailed to determine whether the full text should be retrieved.…”
Section: Resultsmentioning
confidence: 99%
“…After the removal of duplicates, a total of 7080 studies was identified in the search. Following full‐text screening, 71 studies were identified for inclusion, with 23 eligible for meta‐analysis. The abstracts for the majority of the papers were not sufficiently detailed to determine whether the full text should be retrieved.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, results of a controlled trial [91] suggested fasting therapy to be beneficial compared to normocaloric diet in the complex treatment of fibromyalgia. In a further controlled nonrandomized trial [92], we found a beneficial effect of fasting over standard complex treatment in inpatients with fibromyalgia. An uncontrolled study from Germany [62] reported a beneficial effect of fasting on headache frequency and intensity of migraine.…”
Section: Clinical Effects Of Fastingmentioning
confidence: 97%
“…There is preliminary evidence from smaller nonrandomized controlled trials or observational studies for metabolic syndrome [30,31,32,33,34,][50], osteoarthritis [35], fibromyalgia [36], hypertension [37,38,39], chronic pain syndromes of the locomotor system [23,40], migraine [41], enhancement of lifestyle change [42,8] and psychological well-being, support of chemotherapy [43,44], and mood-enhancement [23,45]. …”
Section: Indicationsmentioning
confidence: 99%